Analysis of international climate change governance for the agriculture, forest and land use sector: Gaps and recommendations for future improvement - María Jose Sanz; Ana Karla Perea Blazquez (Earth System Governance, 2025)
The crucial role of land-based activities in climate change mitigation and adaptation has gained recognition under the Paris Agreement, including through the commitments outlined in Nationally Determined Contributions (NDCs). While technical assessments highlight the mitigation potential of the land sector, this potential is constrained by several challenges, particularly competing demands across development, social, environmental and climate objectives. International governance structures for land use often fail to address these multiple objectives, which makes it challenging to ensure sound arbitrages among them. This paper evaluates the current international governance landscape in the Agriculture, Forestry, and Other Land Use (AFOLU) sector, analysing governance functions that address barriers to climate change mitigation globally and assessing the extent to which these functions are met. Our findings indicate that while existing governance frameworks address barriers through guidance, rule-setting, transparency and accountability, support for implementation, and knowledge dissemination, gaps remain, particularly in guidance and signalling, transparency and rules and standards. Other key gaps identified are the insufficiency of the funds mobilised so far, the limitations of global assessments, and the duplicity of efforts and disconnection across different initiatives. Closing these governance gaps is essential to enable effective global governance in the AFOLU sector and unlock its mitigation potential. We propose potential solutions to bridge these gaps.